Pengaruh Terapi Murottal Al-Qur'an terhadap Tekanan Darah Pasien Pre Operasi Katarak dengan Hipertensi di Ruang Tulip Rumah Sakit Daerah dr. Soebandi Jember (The Effect of The Murottal Al-Qur’an Therapy on Blood Pressure of Pre Operative Cataract Patients with Hypertension in Tulip Inpatient Ward of dr. Soebandi Hospital, Jember ) - Siswoyo Siswoyo; Sulis Setyowati; Muhamad Zulfatul A'la (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Cataract is a sight obstruction which causes many cases of blindness in Indonesia. One of the treatment managements of cataract is performed trough sugery. Surgery process may cause anxiety to a patient with sign hypertension. The research aimed to analiyzing the effect of the murottal Al-Qur'an therapy on blood pressure of pre operative cataract patients with hypertension. Independent variable was the murottal Al-Qur'an therapy and dependent variable was blood pressure of pre operative cataract patients with hypertension. The research method was quasi experimental with randomized control group pretest and posttest design. The sampling technique used quota sampling to 30 respondent fulfilled then it used simple random sampling divided into two groups, treatment and control group with 15 respondents for each. Data were analyzed by using Wilcoxon test and Mann Whitney test with 95% of CI. The research results showed that p value of Wilcoxon test in treatment group was 0,000 (systole) and 0,002 (diastole), while control group resulth p value of Wilcoxon test was 0,007 (systole) and 0,317 (diastole). The research results showed that p value of Mann Whitney test in systolic blood pressure category and diastolic blood pressure category was 0,000 for each. Summed up any impact the murottal Al Qur’an to pressure of patient pre cataract surgery by hipertension. Nurses and health workers others could use this POS to reduce patient`s blood pressure with hipertension. Keywords: Murottal Al-Qur'an therapy, Blood pressure, Pre operative, Cataract, Hypertension